About War - Ismail Abdullah (Wacana Seni Journal of Arts Discourse, 2003)
War is for those/persons who love to slaughter someone's rights [not animal's], smell/taste innocent blood, love to siak their own feet into black wines, to eat/share rustty bread, live in concrete cells, to see broken hearts or is about how to erase sombody's name and surname, or his/her skin and colours ...